The Use of Bamboo in Civil Engineering: Sustainability and Innovation at the Max Feffer Center, Pardinho Municipality, São Paulo State (SP), Brazil (Research, Society and Development, 2024)
This research investigates the application of bamboo in civil construction, presenting the Max Feffer Cultural Center case study. This article aims to analyze the use of bamboo in terms of technical, economic, and environmental viability as construction material. the research adopts an integrative approach, combining documentary analysis and case study. The results indicate that bamboo has mechanical properties, such as resistance and flexibility, that make it suitable for large buildings. Furthermore, the material contributes to the energy efficiency of buildings. It has a competitive cost compared to conventional materials, especially in regions where bamboo is abundant and easily accessible, reducing transport and production expenses. However, the study identified challenges, such as the lack of specific regulations and the need for appropriate treatments to guarantee the durability of bamboo in adverse conditions. It is concluded that, despite these challenges, bamboo represents a sustainable alternative to conventional materials, offering environmental and economic advantages. The work reinforces the importance of public policies and regulations that encourage the use of alternative materials in construction, promoting a more ecological and socially responsible practice.